2018
DOI: 10.1002/polb.24765
|View full text |Cite
|
Sign up to set email alerts
|

Entropic effect implication for change in polymer coils swelling state in the demixing enthalpy recovery of aqueous poly(vinyl methyl ether) solutions

Abstract: Time-dependent demixing enthalpy recovery behavior of aqueous poly(vinyl methyl ether) (PVME) solutions exhibits distinct recovery characteristics in three concentration regions. The absence of recovery behavior below a water concentration of 38.3 wt % indicates that the PVME coil is in a globular state. The typically sigmoidal recovery behavior of demixing enthalpy above 38.3 wt % is ascribed to the reswelling of the collapsed polymer coils induced by the entropic effect. The increase in difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 82 publications
(100 reference statements)
2
11
0
Order By: Relevance
“…Moreover, it should be noted that in the previous investigations the determination of entropic contributions in thermodynamic energy term is usually elucidated out from a series of molecules with similar chemical or complex characters, [43][44][45][46][47] in this study and our recent work about PVME aqueous solutions 39 we showed that the entropic effect can be directly determined from a single polymer solution.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Moreover, it should be noted that in the previous investigations the determination of entropic contributions in thermodynamic energy term is usually elucidated out from a series of molecules with similar chemical or complex characters, [43][44][45][46][47] in this study and our recent work about PVME aqueous solutions 39 we showed that the entropic effect can be directly determined from a single polymer solution.…”
Section: Introductionsupporting
confidence: 57%
“…As discussed in the recent work about PVME aqueous solutions, 39 the distinctive demixing enthalpy recovery behaviors in different concentration solutions may be attributed to the entropic effect due to changes in polymer chain swelling states.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations